THE REORDERING IN RURAL SPACE - conceição Walkowski, Marinês; Orige Oliveira, Mirtz; Boneli Vieira, Vinicius; Loch, Carlos (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
The Brazilian rural area has potential for different activities is fundamental reordering in rural targeting the rearrangement of existing properties in an area in order to optimize the use of land observing ecological, social, and economic landscape. The objective of this work is to compare three redevelopment projects in rural areas developed in the highlands of Santa Catarina between 2001 and 2009. Currently the area of the mountain region of Santa Catarina is comprised of a set of eleven municipalities which experienced different methods of reordering.